(untitled) (Bulletin of criminological association of Ukraine, 2023)
This article addresses the importance of effectively combating serious and particularly serious crimes while safeguarding the fundamental right to privacy. It also discusses Ukraine’s commitment to aligning its national legislation and law enforcement practices with European standards, as outlined in Article 8 of the Convention for the Protection of Human Rights and Fundamental Freedoms. The right to private communication is guaranteed by the Constitution of Ukraine and international treaties. Restricting this right during covert investigative activities is only possible on legal grounds and for legitimate purposes. The protection of human rights during these activities is considered a comprehensive system of procedures and rules aimed at minimizing interference and preventing abuse by pre-trial investigation authorities.